Covert infrared image encoding through imprinted plasmonic cavities. Issue 1 (December 2018) - Franklin, Daniel; Modak, Sushrut; Vázquez-Guardado, Abraham; Safaei, Alireza; Chanda, Debashis
Abstract Functional surfaces that can control light across the electromagnetic spectrum are highly desirable. Plasmonic nanostructures can assume this role by exhibiting dimension-tunable resonances that span multiple electromagnetic regimes. However, changing these structural parameters often impacts the higher-order resonances and spectral features in lower-wavelength domains. In this study, we discuss a cavity-coupled plasmonic system with resonances that are tunable across the 3–5 or 8–14 μm infrared bands while retaining near-invariant spectral properties in the visible domain. This result is accomplished by regime-dependent resonance mechanisms and their dependence on independent structural parameters. Through the identification and constraint of key parameters, we demonstrate multispectral data encoding, where images, viewable in the infrared spectral domain, appear as uniform areas of color in the visible domain—effectively hiding the information. Fabricated by large area nanoimprint lithography and compatible with flexible surfaces, the proposed system can produce multifunctional coatings for thermal management, camouflage, and anti-counterfeiting. Undercover images: Hiding in plasmonic sight A new device employing the science of 'plasmonics' allows control over the interaction of various wavelengths of light with its components, with implications for camouflage and anti-counterfeit applications. The device, designed by Debashis Chanda and colleagues of the University of Central Florida, is formed of a dielectric layer patterned with regularly-spaced nano-sized holes, sandwiched between a reflective metallic mirror and a thin upper gold layer with holes corresponding to the middle layer's discs. Images are encoded onto the surface in spun coat films of thermoplastic. Changing the diameters and depths of the holes changes how different wavelengths of light react with the materials. The team was able to tune the device's parameters in a way that made the surface appear as a uniform block of colour unless viewed through an infrared camera over a specific band, when the image can be seen.